Altruism in the hobbit film of “the battle of five armies - Ade Indarto; Sulaiman Sulaiman; Sufiyandi Sufiyandi (Universitas Muara Bungo, 2017)
This research analyzes about altruism found in the Hobbit film “The Batlle of Five Armies”.The Hobbit “The Battle of Five Armies”film is the last film from the Hobbit trilogy which is firstlypublished in 2012, then 2013 for next series and 2014 the last published. The Hobbit is one of filmadapted from the novel John Ronald Reul Tolkien. The Batlle of Five Armies tells about few ofhuman group trying to stay alive from Orcs the enemies of life with help each other. The aims ofthis research is explain type of altruism as found in in the Hobbit film “ The Battle of Five Armies”.This research uses descriptive method, because the datum of this research written on narrative,paragraphs, and descriptive. The writer finds out altruism consist of nepotisti, reiprocal and group.Furthermore, this research uses sociological approach. Sociological approaches help the writer toanalyze in social side.Based on the result, the writer concludes that altruism can happen in eachhuman relationship. There are relationships in family, friends, and groups. Finally, the writer knowsthat altruism can happened both by act and oral speech.